Physical, chemical and natural alternatives to control Meloidogyne spp. in tomato in greenhouse - Avelar Mejía, J. Jesús; Lara Herrera, Alfredo; Llamas Llamas, J. Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of the present work was to evaluate the effectiveness of control of Meloidogyne spp., through the use of physical, chemical and natural alternatives, physics with solarization, chemistry with the nematode Vidate and the natural one by means of the interspersed plantation of cempasuchil (Tagetes erecta) between tomato plants, as well as the combination between the alternatives used. The experiment was carried out in a commercial greenhouse, located in the community of Chaparrosa, municipality of Villa de Cos, Zacatecas, in 2012. An experimental design was used in complete blocks at random with four repetitions and experimental units of a plant. Water, fertilizer and other agrochemicals were applied by drip, with the handling that the producer normally does. Twelve variables were measured, result of count of nematodes, bunches and fruit weight in different dates. The analysis of variance detected significant statistical differences in seven of the variables; with the results and the correlation analysis that was performed among the variables, it was concluded that, with the inclusion of a cempasuchil plant interspersed between tomato plants, as well as this combined treatment with solarization, the lowest number of nematodes and the greater yield of fruits.